Functional and linguistic features of anthroponyms in linguistics - Mustafayeva, Maksad (The Lingua Spectrum, 2025)
This article highlights issues of onomastics, particularly anthroponymy, and analyzes the significance of the naming process in human activity and the role of language in this process. Based on E. Begmatov’s views on the communicative and functional capabilities of language, the process of expressing concepts of objects and phenomena through lexemes is examined. The stages of onomastics development–from ancient scholars to modern researchers–are analyzed. The article provides an etymological and semantic analysis of anthroponyms in Agatha Christie’s “And Then There Were None” and Tokhir Malik’s “Shaytanat”. It identifies the linguistic layers of names in both works and their functional roles in literary texts. The analysis reveals similarities and differences between anthroponyms in English and Uzbek languages and explores methods of character portrayal through names. In conclusion, the role of anthroponyms as a stylistic device in literary works to express the author’s intent is emphasized.